A hexagonal shape-persistent nanobelt of elongated rhombic symmetry with orthogonal π-planes by a one-pot reaction - Lauer, Jochen; Kohl, Bernd; Braun, Felix; Rominger, Frank; Mastalerz, Michael (European journal of organic chemistry, 2022)
Triptycenes with their predefined D3h-symmetry are excellent molecular building blocks to construct shape-persistent nanobelts having π-orbitals orthogonal to the ring plane. However, up to now, there are only a very few examples of fused and rigid iptycene nanobelts synthesized in several consecutive steps in overall yields below 1 %. Here we present the simple one-step one-pot approach to an iptycene nanobelt, which forms in >2 % and can readily be isolated from the polymeric by-product by gel-permeation chromatography.